Governance in Flanders’ regional policy: subregional platforms as development coalitions - Peter Cabus (Belgeo)
Actively engaging citizens is one of the main objectives behind the emergence of governance in the policy making process. The former top-down approach characterized by strong hierarchical relationships and a large distance between policy and citizens, is replaced by an approach that seeks important bottom-up (local) input. New partnerships between non-traditional and political actors are formed in the decision making process in order to engage citizens.Since the 1990s, the governance idea has gradually become a central focus of regional development policy. One of the driving forces behind this development is certainly the politically friendly nature of global-local theory. It provides local politicians with an external enemy (the global) and a solution (the mobilization of local actors in development coalitions). From this perspective, this paper analyses the developments in Europe and especially in Flanders, where sub-regional platforms act as development coalitions.The paper concludes that these platforms contribute to a governance structure that enables genuine public participation in policy making. At the same time, it offers a more sceptical assessment of the impact of development coalitions on economic processes. Territorial identification is a tangible outcome of the process, whilst the notion of localized knowledge spillovers is confined to academic speculation.